The effect of coffee-enriched chlorogenic acid on insulin, GIP and GLP-1 levels in healthy humans: a systematic review - Faraji, Hossein (Progress in Nutrition, 2019)
Background: There are different supplements in the drug stores in order to prevent and treat some diseases. Chlorogenic acid is one of the polyphenolic compounds affected insulin, GIP and GIP-1 to animal study as the prevention factors for diabetes, while human studies show conflict results in this regard. As regard to the lack of systematic review investigated on this topic, the purpose of this study is to assess this issue. Materials and Methods: Systematic search was conducted in the databases of google scholar, Science direct, PubMed and web of knowledge by the end of Feb. of 2017. Keywords for the pub med database included: “Chlorogenic Acid”, “Green coffee”, “Coffee”, “GIP”, “GLP-1” and “Insulin”. Also, the qualitative assessment of studies was done by the jadad table. Results: 1631 studies were found, after the searching based on research literature. Then, 8 studies were entered into the qualitative synthesis stage after classifying studies based on duplication and eligibility criteria. The results of studies showed no significant effect of the chlorogenic acid in the form of coffee extracts on blood insulin concentration. In additions, GIP was decreased in one study and GLP-1 was increased in another one study, due to the use of coffee extracts-enriched chlorogenic acid. Conclusions: Our findings demonstrated that the consumption of Chlorogenic acid may be has lowering effect on GIP, and increasing effect on GLP-1, while has not effect on insulin, but as regard to the lack of enough studies, it has needed further study in future.